Feeding back research results – Changes in principal and teacher narratives about student participation. (June 2020) - Zala-Mezö, Enikö; Datnow, Amanda; Müller-Kuhn, Daniela; Häbig, Julia
Highlights: Introducing a way how research results can be fed back to schools. Feedback of research results is a specific form of data use in schools. Feedback changes teachers' perception of the topic and induces changes in school. Closing the gap between research and practice – using results to improve schools. Abstract: Schools are among the most studied organizations, yet research has little influence on them. This is in part because schools often do not have an opportunity to learn from the research projects they are engaged in. In this paper, we explain the process and impact of feeding back research results to participating schools. The feedback of results related to the topic of student participation was designed in a school-specific way and expected to support school improvement processes. Accordingly, we examined changes in beliefs and school practices by analysing longitudinal qualitative interviews. Results show changes in school practices and in the perceived importance of student participation, as well as enduring beliefs that inhibited changes. The findings of this paper contribute to the discourse on data use in education and to building research-practice-partnerships.